Socio-pragmatic Functions of Code-switching in Latino Essays. A Case Study on Bilingual Pragmatic Markers in Susana Chávez-Silverman's Killer Crónicas (2004). - ENGHELS, RENATA (Bulletin of Hispanic Studies (1475-3839), 2018)
This paper contributes to the general discussion on the value of written data for the study of phenomena typical of orality, and wants to provide a better understanding of the social and linguistic functions of code-switching in Chicano narratives. It looks into the use of bilingual pragmatic marker pairs in Susana Chávez-Silverman's essays Killer Crónicas (2004). Two case studies are dedicated to pragmatic expressions that focus on the direct interaction between the speaker-writer and hearer-reader, namely the epistemic markers you know/ sabes and the metadiscursive parentheticals I swear/ te lo juro. It is shown that, besides supporting well thought literary effects, the use of pragmatic markers in this volume mirrors surprisingly well their use in monolingual and bilingual spoken discourse. As a consequence, due to its high degree of orality, the text of Chávez-Silverman can be considered as a complementary source for the study of code-switching in spoken language.